Mercury Deposition, Climate Change and Anthropogenic Activities: A Review - Li, Feng; Ma, Chunmei; Zhang, Pingjiu (Frontiers in Earth Science, 2020)
As a toxic and harmful global pollutant, mercury enters the environment through natural sources and human activities. Based on large numbers of previous studies, this paper summarizes the characteristics of mercury deposition, the impact of climate change and human activities on mercury deposition from a global perspective. The results indicate that the mercury accumulation level was relatively low before the Industrial Revolution of 1840, while after the industrialization, intensive industrial activities produced large amounts of anthropogenic mercury emissions and the accumulation increased rapidly. The cold climate is conducive to the accumulation of mercury, whereas the warm climate works to the disadvantage of mercury accumulation. Before the industrialization, the kustelite and mercury mining and the widespread use of cinnabar were the main sources of anthropogenic mercury; After the industrialization, the coal combustion, the non-ferrous metal smelting, the waste incineration and the chlor-alkali industry development have led to a significant increase in anthropogenic emissions of mercury, which in turn has caused a sharp increase in mercury deposition. Through analysis, the author finds that most of the research areas are distributed in the Northern Hemisphere, including Europe, North America and China of Asia, but only in parts of the Southern Hemisphere, including South America, Africa and Antarctica; The study mainly focuses on the time scales since the Holocene, and there are not many studies focusing on the time scales before the Holocene; The natural record bodies widely used in the previous studies are fen peat and lacustrine deposits. The ice core records with higher resolution are very few, and there are almost no stalagmite records. Since few studies have been conducted on the relationship between precipitation change and mercury accumulation, the impact of climate change, especially the impact of humidity change on the mercury accumulation mechanism has not yet been deeply studied. Therefore, due to the fact that the research spots are unevenly distributed, the mercury deposition records with the longer time scales and higher resolution are not available and the study on relationship between precipitation and mercury accumulation is not deep enough, the relevant research needs to be further carried out.